Familial Exudative Vitreoretinopathy-Related Disease-Causing Genes and Norrin/β-Catenin Signal Pathway: Structure, Function, and Mutation Spectrums - Hongtao Xiao; Yuna Tong; Yuxuan Zhu; Min Peng (Journal of Ophthalmology)
Familial exudative vitreoretinopathy (FEVR) is a hereditary ocular disorder characterized by incomplete vascularization/abnormality of peripheral retina. Four of the identified disease-causing genes of FEVR were NDP, FZD4, LRP5, and TSPAN12, the protein coded by which were the components of the Norrin/β-catenin signal pathway. In this review, we summarized and discussed the spectrum of mutations involving these four genes. By the end of 2017, the number of FEVR causing mutations reported for NDP, FZD4, LRP5, and TSPAN12 was, respectively, 26, 121, 58, and 40. Three most frequently reported mutations were c. 362G > A (p.R121Q) of NDP, c. 313A > G (p.M105V), and c.1282_1285delGACA (p.D428SfsX2) of FZD4. Mutations have a tendency to cluster in some “hotspots” domains which may be responsible for protein interactions.